Reinventar la nación a partir de la fe católica. De la religión, el clero y la política en la guerra civil de 1851 (2008)
ABSTRACT: By the mid-nineteenth century in Colombia, the Liberals raised the power of the state, from where they led a series of reforms, aimed to modernizing the country, which involved breaking the old powers of the aristocratic elite and the Catholic Church, and promotion of the values of secular, democratic and nascent capitalism as the foundations of social order. In the midst of radicalization and militarization of the conflict, the church was identified with the conservative party, both sacred war with the announcement of it as a crusade for national redemption and updated the combative and militant faith of the universal Catholic tradition. The Conservative assimilated its claim of the Catholic faith with the salvation of the internal political order, a way to reinvent the nation from its position and pre-modern traditions, which was foundated in the principles of Catholicism. The non differentiation between the conservative discourse and church and religion, provided the incendiary participation of clergy and the Catholic people in the war, but in the long term, it complicated relations between Church and State. In the same way, with war, political activity was fulfilled as a messianic and sacred character that has deeply marked national political history, and the close and trimmed representations of nation were visible, those that built the political parties, as they had no place for the opponents. But during the War of the Supreme (1839-1842) religious motives were already present; it was with the War of 1851 that the Colombian Church started its troubled relationship with modernity, at least from the interpretation of anticlerical liberalism.